Arbitration as an Alternative to Resolving Industrial Relations Disputes on Employment Rights in Indonesia: A Restorative Justice Approach - Kurniasih Bahagiati; Walid Fajar Antariksa (Journal of Progressive Law and Legal Studies, 2026)
The resolution process in the Industrial Relations Court, conducted by judges or ad hoc judges, often takes a long time, involves high costs, and frequently ends with decisions that leave one party dissatisfied and disadvantaged. Therefore, a mechanism for resolving industrial relations disputes that is quick, accurate, fair, and inexpensive, harmonious, dynamic, and supported by official institutions is needed. The purpose of this study is to examine the concept of arbitration as one of the alternatives for resolving industrial relations disputes and to understand it from the perspective of restorative justice. This study uses a normative juridical method, with a legislative approach and a conceptual approach. The primary data for this study are laws and regulations, specifically Law No. 2 of 2004 on the Resolution of Industrial Relations Disputes, as well as related official documents. The secondary data in this study are legal literature and academic journals on the resolution of industrial relations disputes and restorative justice. Research results show that arbitration is the best mechanism for resolving industrial disputes because its decisions are final and binding, unlike mediation, whose outcomes are advisory and not binding. Arbitration also differs from the long-standing, complex, and costly Industrial Relations Court. The concept of arbitration as an alternative method for resolving industrial disputes aligns with the restorative justice approach, which focuses on restoring the relationship between workers/laborers and employers. This study contributes to the development of legal scholarship on industrial relations dispute resolution by offering a restorative justice perspective on arbitration as an effective, efficient, and relationship-oriented mechanism.